2004
DOI: 10.1016/j.lungcan.2004.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, comorbidity and performance status on the choice of treatment for patients with non-small cell lung cancer; results of a population-based study

Abstract: SummaryBackground: In the Netherlands in 1997, 43% of patients with newly diagnosed lung cancer were over 70. Large age-specific differences in treatment exist. We examined whether age, comorbidity, performance status and pulmonary function influenced treatment. Patients and methods: Data on patients with newly diagnosed non-small cell lung cancer (N = 803) were obtained: comorbidity, performance status, pulmonary function (FEV1) and initial treatment. Age-specific differences in treatment according to the gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
65
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 26 publications
8
65
1
Order By: Relevance
“…Several studies showed that comorbid conditions may play an important role in decisionmaking among cancer patients. 15,20,21 Chemotherapy is considered more effective in patients with predominantly lymph node/pleural metastases from CUP, whereas it offers only limited benefit to patients with liver, bone, or multiple organ involvement. 6 These data suggest that the site of metastasis may influence the decision to administer chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that comorbid conditions may play an important role in decisionmaking among cancer patients. 15,20,21 Chemotherapy is considered more effective in patients with predominantly lymph node/pleural metastases from CUP, whereas it offers only limited benefit to patients with liver, bone, or multiple organ involvement. 6 These data suggest that the site of metastasis may influence the decision to administer chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several studies have demonstrated that comorbid conditions also may play an important role in decision making. 15,20,21 To reconcile the different outcomes reported by registries and referral centers, we conducted a population-based clinical analysis of consecutive patients with CUP in the Northern Alberta Cancer Registry from 2000 to 2003 to investigate how comorbid conditions, PS, and age may influence the choice of chemotherapy and the prognosis of patients with CUP.…”
mentioning
confidence: 99%
“…This is seen across all tumor types but is of particular importance in lung cancer where the median age at diagnosis is 68 years (21,22). Also the geriatric patients merit additional careful consideration in view of higher prevalence of co-morbidities and depletion of their physiological reserve which affects therapy adversely.…”
Section: Discussionmentioning
confidence: 99%
“…29 Chemotherapy use declined dramatically with increasing age at diagnosis, consistent with previous findings. 30,31 This may be because of physicians' perception of decreased chemotherapy tolerance or increased risks of toxicity in elderly patients. 30 Older patients with lung cancer often are compromised by the surgery itself and have a prolonged recovery time compared with other cancer operations, such as mastectomy and colectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This may interfere with the receipt of chemotherapy. Elderly patients also may be reluctant to trade quality of life for a perceived survival benefit 31 and may be more likely to refuse chemotherapy. 32,33 We observed significant associations between disease stage and the receipt of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%